2010
DOI: 10.2214/ajr.08.1022
|View full text |Cite
|
Sign up to set email alerts
|

Resectability of Pancreatic Adenocarcinoma in Patients with Locally Advanced Disease Downstaged by Preoperative Therapy: A Challenge for MDCT

Abstract: Sensitivity for prediction of resectability tends to be lower for patients with locally advanced pancreatic cancer that has been downstaged by neoadjuvant therapy, but this trend is not statistically significant. Interobserver variability for determination of resectability is statistically higher than for controls who did not receive preoperative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 24 publications
2
31
0
3
Order By: Relevance
“…The search yielded 649 studies of which 15 published between 2009 and 2017 were included in the final analysis (Fig. ) . These 15 studies included 995 patients with BRPC ( n = 683) and locally advanced ( n = 312) PDAC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search yielded 649 studies of which 15 published between 2009 and 2017 were included in the final analysis (Fig. ) . These 15 studies included 995 patients with BRPC ( n = 683) and locally advanced ( n = 312) PDAC.…”
Section: Resultsmentioning
confidence: 99%
“…Morgan et al . used the term downstaging of PDAC to indicate conversion from a locally advanced nonresectable lesion to a lesion that appeared potentially resectable on CT, because of improvement in vascular encasement, regardless of tumour size change.…”
Section: Methodsmentioning
confidence: 99%
“…Also the study of Cassinotto et al [41] confirmed the decrease in the diagnostic performance of the CT to reevaluate resectability after neoadjuvant therapy of pancreatic tumor. Morgan [42] demonstrated that the CT sensitivity for prediction of resectability tends to be lower for patients with locally advanced pancreatic cancer that has been downstaged by neoadjuvant therapy than for controls who did not receive preoperative therapy. In patients undergoing chemo radiotherapy the most limits of CT is differentiating a residual tumor from the fibro-inflammatory tissue, so other techniques are needed to optimally evaluate the tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…Daher sollten allein von der Bildgebung nur Tumoren mit kompletter Ummauerung der Gefäße über einige Zentimeter oder mit deutlicher Lumenverengung der Arterie als nichtresektabel eingestuft werden [33]. Liegt ein lokal fortgeschrittener, primär nichtresektabler Befund vor, sollte bei diesen Patienten in neoadjuvanter Intention eine Chemotherapie (ggf.…”
Section: Der Onkologe 11 · 2015unclassified
“…AMS A. mesenterica superior, VMS V. mesenterica superior grund der ausgeprägten desmoplastischen Reaktion des Pankreaskarzinoms wird die reale Tumorausdehnung bildgebend (CT/ MRT) jedoch häufig überschätzt [27]. Daher sollten allein von der Bildgebung nur Tumoren mit kompletter Ummauerung der Gefäße über einige Zentimeter oder mit deutlicher Lumenverengung der Arterie als nichtresektabel eingestuft werden [33]. Liegt ein lokal fortgeschrittener, primär nichtresektabler Befund vor, sollte bei diesen Patienten in neoadjuvanter Intention eine Chemotherapie (ggf.…”
Section: Lokal Nichtresektable Pankreastumorenunclassified